Factors related to the association of social anxiety disorder and alcohol use among adolescents: a systematic review - Elisabeth Lima Dias da Cruz; Priscila Diniz de Carvalho Martins; Paula Rejane Beserra Diniz (Elsevier, 2017)
Objective: To identify the risk factors related to the association between social anxiety disorder and alcohol use in adolescents. Source of data: The PICO research strategy was used to perform a systematic review in Medline, LILACS, Pubmed, IBECS and Cochrane Library databases. DeCS/MeSH: Phobic Disorders, Adolescent, Behavior, Ethanol, Risk Factors, and the Boolean operator "AND" were used. Inclusion criteria were: cross-sectional, prospective/retrospective cohort, and case-control studies, carried out in adolescents (10-19 years), original articles on social anxiety disorder and alcohol use published between 2010 and 2015. Studies that did not report the terms "anxiety disorder" and "alcohol use" in the title and abstract were excluded. Synthesis of data: 409 articles were retrieved; after the exclusion of 277 repeated articles, the following were eligible: 94 in MEDLINE, 68 in Pubmed, 12 in IBCS, and three in LILACS. Titles and abstracts were independently read by two examiners, which resulted in the selection of eight articles for the analysis. Risk factors associated to the two disorders were female gender, age, peer approval and affective problems for alcohol use, confrontation situations and/or compliance reasons, frequency of alcohol use, and secondary comorbidities, such as depression and generalized anxiety. Conclusions: It is necessary to assess the period of social anxiety disorders first symptom onset, as well as the risks for alcohol use in order to establish corrective intervention guidelines, especially for socially anxious students. Resumo: Objetivo: Identificar os fatores de risco relacionados a associação entre o transtorno de ansiedade social e uso de álcool entre adolescentes. Fontes dos dados: Utilizou-se a estratégia de pesquisa PICO para realizar a revisão sistemática nas bases Medline, LILACS, Pubmed, IBECS e Biblioteca Cochrane. Foi utilizado os DeCS/MeSH: Transtornos Fóbicos, Adolescente, Comportamento, Etanol, Fatores de Risco e o operador boleano "AND". Os critérios de inclusão foram: estudo transversal, coorte prospectiva/retrospectiva e caso-controle, realizados em adolescentes (10 a 19 anos), artigos originais sobre transtorno de ansiedade social e uso de álcool publicado entre 2010 a 2015. Excluíram-se os estudos que não referiam transtorno de ansiedade e uso de álcool no título e no resumo. Síntese dos dados: 409 artigos foram identificados e após exclusão repetidos 277 estudos foram elegíveis: 94 no MEDLINE, 68 em Pubmed, 12 IBCS e 3 LILACS. Foi realizada a leitura dos títulos e resumos de forma independente por dois examinadores, que resultou na seleção de 8 artigos para análise. Fatores de riscos associados aos dois transtornos: predominância do gênero feminino, idade, aprovações pelos pares e problemas afetivos para o uso de álcool, situações de enfrentamentos e/ou motivos de conformidades, frequência de uso do álcool e comorbidades secundárias como depressão e ansiedade generalizada. Conclusões: É necessário avaliar o período de surgimento dos primeiros sintomas de transtorno de ansiedade social e dos riscos para o uso de álcool e instituir normas corretivas de intervenções, principalmente para os alunos socialmente ansiosos. Keywords: Phobic disorders, Adolescent, Behavior, Ethanol, Risk factors, Palavras-chave: Transtornos fóbicos, Adolescente, Comportamento, Etanol, Fatores de risco